Implementing the SDGs Program for Sustainable Village Development Through Sharia Principles in Mataraman Sub-District - Muhammad Hendri Yanova; Rahmatul Huda; Parman Komarudin; Arif Rahmatillah; Salbilla Norsyifa (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2024)
This research aims to analyse the policy implementation of the Village Sustainable Development Goals programme in an effort to achieve sustainable development in Mataraman Sub-district. The research method used is qualitative research with data collection through field observations, interviews, and analysis of policy documents. The results show that the implementation of the Village Sustainable Development Goals policy in Mataraman Sub-district has had a positive impact in several aspects, such as improving the quality of education, access to health, and better management of natural resources. There are two villages that focus on village SDGs, namely Takuti village and Gunung Ulin village. Mataraman sub-district itself has programmes that focus on indicators such as poverty (1), decent work and economic growth (8), infrastructure (9), education (4), sanitation and clean water (6), health (3), and dynamic village institutions and adaptive village culture (18). However, there are also some obstacles such as budget limitations, lack of community participation, and coordination between institutions that still need to be improved. In terms of sharia principles, this implements the values of sharia principles, namely Al-'Adālah, Al-Maṣlaḥah, Al-‘Amal, and Al-Mas'ūliyyah.